Analyses of Recombinant Stereotypic IGHV3-21–Encoded Antibodies Expressed in Chronic Lymphocytic Leukemia - Ghia, Emanuela M. (J Immunol, 2011)
Chronic lymphocytic leukemia (CLL) cells that use IgH encoded by IGHV3–21 and that have a particular stereotypic third CDR (HCDR3), DANGMDV (motif-1), almost invariably express Ig L chains (IgL) encoded by IGLV3–21, whereas CLL that use IGHV3–21–encoded IgH with another stereotypic HCDR3, DPSFYSSSWTLFDY (motif-2), invariably express κ-IgL encoded by IGKV3–20. This nonstochastic pairing could reflect steric factors that preclude these IgH from pairing with other IgL or selection for an Ig with a particular Ag-binding activity. We generated rIg with IGHV3–21–encoded IgH with HCDR3 motif-1 or −2 and IgL encoded by IGKV3–20 or IGLV3–21. Each IgH paired equally well with matched or mismatched κ- or λ-IgL to form functional Ig, which we screened for binding to an array of different Ags. Ig with IGLV3–21–encoded λ-IgL could bind with an affinity of ~2 × 10(−6) M to protein L, a cell-wall protein of Peptostreptococcus magnus, independent of the IgH, indicating that protein L is a superantigen for IGLV3–21–encoded λ-IgL. We also detected Ig binding to cofilin, a highly conserved actin-binding protein. However, cofilin binding was independent of native pairing of IgH and IgL and was not specific for Ig with IgH encoded by IGHV3–21. We conclude that steric factors or the binding activity for protein L or cofilin cannot account for the nonstochastic pairing of IgH and IgL observed for the stereotypic Ig made by CLL cells that express IGHV3–21. The Journal of Immunology, 2011, 186: 000–000.